Ecological Land Suitability of Goats in The Highland Region - Cori Qamara; Dani Nur Arifin; Andi Nurmasytha; Karenina Dwi Yulianti; Kirana Dara Dinanti Adiputra; Aditya Alqamal Alianta (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2024)
Goat farming has a lot of promise in the highland area of Limapuluh Kota Regency in West Sumatra. However, ecological pressure may result from goat population development that is not balanced with land suitability assessments. Goats’ ecological land suitability will be examined in this study using biophysical, socioeconomic, and environmental carrying capacity metrics. The research methodology include field surveys, local farmer participation, and geographic analysis utilizing Geographic Information Systems (GIS). The findings indicated that 91.7% of the district of Limapuluh Kota is suitable for goat rearing. Because of the land elevation over 1,500 meters above sea level and the excessive rainfall exceeding 2,500 mm, 8.3% of the area is categorized as not suitable (N). According to the study’s findings, the growth of goat farming in Limapuluh Kota District must take ecological zoning into account, giving precedence to land areas that are appropriate for intense development and the use of silvopastura systems. These results offer a solid foundation for planning cattle sustainably in tropical highlands.